Chemical proteomic identification of functional cysteines with atypical electrophile reactivities. (16th March 2021) - Litwin, Kevin; Crowley, Vincent M.; Suciu, Radu M.; Boger, Dale L.; Cravatt, Benjamin F.
Graphical abstract: Highlights: Structurally diverse electrophiles screened for cysteine reactivity in the proteome. Atypical electrophile-cysteine interactions discovered for several proteins. Liganded cysteines found at sites for catalysis and protein-protein interactions. Abstract: Cysteine-directed covalent ligands have emerged as a versatile category of chemical probes and drugs that leverage thiol nucleophilicity to form permanent adducts with proteins of interest. Understanding the scope of cysteines that can be targeted by covalent ligands, as well as the types of electrophiles that engage these residues, represent important challenges for fully realizing the potential of cysteine-directed chemical probe discovery. Although chemical proteomic strategies have begun to address these important questions, only a limited number of electrophilic chemotypes have been explored to date. Here, we describe a diverse set of candidate electrophiles appended to a common core 6-methoxy-1, 2, 3, 4-tetrahydroquinoline fragment and evaluate their global cysteine reactivity profiles in human cancer cell proteomes. This work uncovered atypical reactivity patterns for a discrete set of cysteines, including residues involved in enzymatic catalysis and located in proximity to protein–protein interactions. These findings thus point to potentially preferred electrophilic groups for site-selectively targeting functional cysteines in the human proteome.